Maltodextrin-induced intestinal injury in a neonatal mouse model - Pratibha Singh; Lady Leidy Sanchez-Fernandez; David Ramiro-Cortijo; Pedro Ochoa-Allemant; George Perides; Yan Liu; Esli Medina-Morales; William Yakah; Steven D. Freedman; Camilia R. Martin (The Company of Biologists, 2020)
Prematurity and enteral feedings are major risk factors for intestinal injury leading to necrotizing enterocolitis (NEC). An immature digestive system can lead to maldigestion of macronutrients and increased vulnerability to intestinal injury. The aim of this study was to test in neonatal mice the effect of maltodextrin, a complex carbohydrate, on the risk of intestinal injury. The goal was to develop a robust and highly reproducible murine model of intestinal injury that allows insight into the pathogenesis and therapeutic interventions of nutrient-driven intestinal injury. Five- to 6-day-old C57BL/6 mice were assigned to the following groups: dam fed (D); D+hypoxia+Klebsiella pneumoniae; maltodextrin-dominant human infant formula (M) only; M+hypoxia; and M+hypoxia+K. pneumoniae. The mice in all M groups were gavage fed five times a day for 4 days. Mice were exposed to hypoxia twice a day for 10 min prior to the first and last feedings, and K. pneumoniae was added to feedings as per group assignment. Mice in all M groups demonstrated reduced body weight, increased small intestinal dilatation and increased intestinal injury scores. Maltodextrin-dominant infant formula with hypoxia led to intestinal injury in neonatal mice accompanied by loss of villi, increased MUC2 production, altered expression of tight junction proteins, enhanced intestinal permeability, increased cell death and higher levels of intestinal inflammatory mediators. This robust and highly reproducible model allows for further interrogation of the effects of nutrients on pathogenic factors leading to intestinal injury and NEC in preterm infants. This article has an associated First Person interview with the first author of the paper.